2021
DOI: 10.1007/s13412-021-00679-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessing perceptions and priorities for health impacts of climate change within local Michigan health departments

Abstract: Climate change affects Michigan’s public health in several primary ways, including increased incidences of vector-borne, waterborne, heat-related, and respiratory illness. Because local health departments (LHDs) play a central role in surveillance and preventative health services, they are among the first institutions to contend with the local impacts of climate change. To assess current perceptions among Michigan public health officials, an online survey was conducted in partnership with the Michigan Associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Specifically, the objectives for the majority of literature reviewed could be categorized as either method development, enhancement or testing. Secondary objectives included improving the efficiency, effectiveness, and sustainability of PHEM decisions ( 1 , 16 , 17 ). Other objectives highlighted in the research include reducing morbidity, and mortality as consequence of threats emerging, and preserving PH resources ( 18 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Specifically, the objectives for the majority of literature reviewed could be categorized as either method development, enhancement or testing. Secondary objectives included improving the efficiency, effectiveness, and sustainability of PHEM decisions ( 1 , 16 , 17 ). Other objectives highlighted in the research include reducing morbidity, and mortality as consequence of threats emerging, and preserving PH resources ( 18 ).…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, the components of an RR should be fit-for-purpose and integrated within organizational planning cycles and decision-making processes ( 25 , 47 ). Planning is needed to guarantee that the threat ranking exercise is matched to organizational objectives and developed with established BP and principles ( 16 , 19 , 25 , 27 ). For planning to be effectively supported it is critical that senior management is engaged from the onset, so that objectives and priorities are clearly defined ( 13 , 16 , 27 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Michigan, USA, public health officials acknowledged the presence of climate-related health issues in their regions, such as heatwaves and air quality concerns. Nevertheless, only a minority considered climate change to be a top priority in their policymaking (Carter et al, 2021). Similarly, a 2012 survey of local health department officials in New York, USA, found that only about four out of ten (39%) participants believed climate change will be a public health concern in the next 20 years, and only one-quarter (25%) believed it was a priority for their department (Carr et al, 2012).…”
Section: Understanding Of and Engagement With Climate Change And Heal...mentioning
confidence: 99%